Optoelectronic behavioral study of defect-chalcopyrite semiconductors XGa2Te4 (X = Zn, Cd). (February 2017) - Kumar, Pancham; Soni, Amit; Bhamu, K.C.; Sahariya, Jagrati
Graphical abstract: Highlights: Most accurate electronic & optical properties of ZnGa2 Te4 & CdGa2 Te4 are computed. First ever optical properties of ZnGa2 Te4 using mBJ within FP-LAPW. The origin of complex dielectric functions is explained using energy bands. Utility in Solar cell and photovoltaic is discussed in terms of absorption coefficients. Abstract: In this work, electronic structure and optical properties investigations for defect-chalcopyrite semiconductors ZnGa2 Te4 and CdGa2 Te4 are presented using full potential linearized augmented plane wave method. Energy bands and density of states (DOS) computations are performed using different flavors of exchange and correlations. The calculations are performed using Wu-Cohen generalized gradient approximation (WC-GGA), Perdew et al. (PBE-sol) and the most accurate modified Becke and Johnson (mBJ) potentials. Our investigations show that energy bands and DOS computed using mBJ potential are in better agreement with the available experimental data. Optical properties such as, dielectric tensor components, absorption spectra, reflectivity, refractivity, dielectric loss, are investigated using mBJ potential. Imaginary peaks of di-electric tensor ε 2 ( ω ), are interpreted by means of inter-band transitions from valence to conduction band. High intensity absorption curves from 3 to 5 eV, energy band gap depicted for ZnGa2 Te4 (1.61 eV) and CdGa2 Te4 (1.78 eV) materials indicates their applicability for solar photovoltaic and other optoelectronic applications.